Hydrological changes in subarctic Russian peatlands during the last millennia due to climate change - Boxström, Agneta (Helsingin yliopisto, 2021)
Abstract: Northern boreal peatlands form one of the biggest carbon pools in the biosphere, thus having great potential to cause major changes to the global carbon cycle. The ongoing recent warming may affect the carbon dynamics though factors, such as, vegetation, hydrology and permafrost balance. As the future is still uncertain there are no definitive answers on how the peatlands will react in the future. Fortunately, moisture sensitive organisms such as, bryophytes and testate amoeba is preserved in the peat and can therefore be used to reconstruct past climatic shifts. In this thesis I studied palaeohydrology and peat accumulation over the last two millennia, from three peat cores originating in a permafrost peatland in Rogovaya, Russia. I used testate amoeba as a proxy of past moisture conditions and plotted the taxa composition of each core against 14C and 210Pb dated samples, to reconstruct past moisture shifts. The results were also supplemented by plant macrofossil and carbon accumulation data for more robust results. Of the three cores, Rog11 provided the oldest testate amoeba dataset by reaching the Dark Ages Cold Period. During this period there were indications of dry moisture conditions followed by a wet Medieval Warm Period. The Little Ice Age gave indications of a drying trend, while toward the end of the LIA Rog8 indicated opposite moisture conditions. From the end of the LIA onwards a general trend of drying and increased carbon accumulated is noted. Yet, during the last decade the trend has turned. The wet shift might indicate that the threshold for the peatland has been reached and the amount of melting permafrost has exceeded the evapotranspiration rate. As a conclusion my result indicates that the dynamics of both hydrology and carbon are complicated processes affected by both autogenic and allogenic factors, therefore causing large variability even on a local scale. The absence of widely spread observations of the most recent wet shift also indicates that the response of the peatland to ...